A Theory of Strategic Voting in Runoff Elections - Bouton, Laurent (American Economic Review, 2013)
This paper analyzes the properties of runoff electoral systems when voters are strategic. A model of three-candidate runoff elections is presented, and two new features are included: the risk of upset victory in the second round is endogenous, and many types of runoff systems are considered. Three main results emerge. First, runoff elections produce equilibria in which only two candidates receive a positive fraction of the votes. Second, a sincere voting equilibrium does not always exist. Finally, runoff systems with a threshold below 50 percent produce an Ortega effect that may lead to the systematic victory of the Condorcet loser. (JEL C72, D72)